Battery cell, method of manufacturing the same, separator, battery device, and electric device

CN122992283APending Publication Date: 2026-10-27CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510534267.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-27
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

为改善隔膜热收缩问题,行业常采用勃姆石或氧化铝作为耐热填料和粘合剂搭配来构建耐热保护涂层,但氧化铝或勃姆石等耐热涂层本身不具备吸收和保持电解液的能力

Benefits of technology

[0015]本申请可利用包括多孔纤维素颗粒的原料获得浆料然后直接用于涂覆基膜,因此可与常规隔离膜制备的流程兼容,易于工业推广应用。由于纤维素颗粒的疏松多孔结构,实现隔离膜对电解液的高吸液浸润性,而且多孔纤维素颗粒相对于纤维素直接使用更耐压因此孔隙保存度较好,提高了隔离膜整体的保液能力,从而改善电池在后续循环过程中的局部贫液和拐角析锂的现象,减少容量骤降的风险。同时,相较于常用的勃姆石与氧化铝颗粒等无机耐热颗粒,多孔纤维素颗粒的重量更低,可提升电池单体的能量密度。另外,多孔纤维素颗粒相对于无机耐热颗粒与涂层中的粘结剂等有机材料的相容性更好,因此更有利于粘结剂粘结作用的发挥,进而可以在实现相同粘结效果的基础上减少粘结剂的用量,从而进一步提高电池单体的质量能量密度,或者使用相同用量的粘结剂改善隔离膜与极片的粘结效果从而改善电池单体的循环性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992283A_ABST
    Figure CN122992283A_ABST
Patent Text Reader

Abstract

The application provides a battery monomer, a preparation method thereof, a separator, a battery device and a power utilization device to improve the cycle performance of the battery monomer. The battery monomer comprises a positive electrode sheet, a negative electrode sheet and a separator between the positive electrode sheet and the negative electrode sheet, and the separator comprises a base film and a coating layer on at least one side of the base film, wherein the coating layer comprises porous cellulose particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery technology, and in particular to a battery cell and its preparation method, a separator, a battery device, and an electrical device. Background Technology

[0002] The separator is a structure in a battery cell used to isolate the positive and negative electrodes. Because battery cells release heat during charge-discharge cycles, the separator needs to have heat resistance to prevent thermal shrinkage and short circuits between the positive and negative electrodes. To improve the thermal shrinkage problem of the separator, the industry often uses boehmite or alumina as heat-resistant fillers and binders to construct a heat-resistant protective coating. However, heat-resistant coatings such as alumina or boehmite themselves do not have the ability to absorb and retain electrolyte. Furthermore, boehmite or alumina have a high density, which affects the energy density of the battery cell and increases raw material costs. Summary of the Invention

[0003] This application provides a battery cell and its preparation method, a separator, a battery device, and an electrical device to improve the cycle performance of the battery cell.

[0004] A first aspect of this application provides a battery cell including a positive electrode, a negative electrode, and a separator between the positive and negative electrodes. The separator includes a base film and a coating on at least one side of the base film, wherein the coating includes porous cellulose particles.

[0005] This application provides a coating comprising porous cellulose particles on at least one side of the base membrane. The electrolyte enters the porous structure of the cellulose particles, achieving high electrolyte absorption and wettability of the separator. Furthermore, the porous cellulose particles are more pressure-resistant than directly using cellulose, resulting in better porosity retention and improving the overall electrolyte retention capacity of the separator. This mitigates localized electrolyte depletion and lithium plating at corners during subsequent cycles, reducing the risk of sudden capacity drops and improving the cycle performance of individual battery cells. Simultaneously, compared to commonly used inorganic heat-resistant particles such as boehmite and alumina, porous cellulose particles are lighter, increasing the gravimetric energy density of the battery cells. Additionally, porous cellulose particles exhibit better compatibility with organic materials such as binders in the coating compared to inorganic heat-resistant particles, thus facilitating the bonding effect of the binder. This allows for a reduction in the amount of binder used while achieving the same bonding effect, further improving the gravimetric energy density of the battery cells. Alternatively, the same amount of binder can be used to improve the bonding effect between the separator and the electrode, thereby improving the cycle performance of the battery cells.

[0006] In any embodiment of the first aspect of this application, the porosity of the separator is 44%-53%.

[0007] In any embodiment of the first aspect of this application, the porous cellulose particles are spherical particles or near-spherical particles.

[0008] In any embodiment of the first aspect of this application, the sphericity of the porous cellulose particles is 0.83-0.91.

[0009] In any embodiment of the first aspect of this application, the average particle size of the porous cellulose particles is 10-16 μm.

[0010] In any embodiment of the first aspect of this application, the porous cellulose particles include any one or more of plant cellulose particles or bacterial cellulose fiber particles.

[0011] In any embodiment of the first aspect of this application, the coating further includes inorganic heat-resistant particles.

[0012] In any embodiment of the first aspect of this application, the weight ratio of porous cellulose particles to inorganic heat-resistant particles in the coating is (10-60):(90-40), optionally 30-60:70-40.

[0013] The second aspect of this application provides a method for preparing a battery cell, including a process for preparing a separator, the process comprising:

[0014] Raw materials including porous cellulose particles, dispersant and binder are mixed to obtain a slurry; and the slurry is placed on at least one side of a base membrane and dried to obtain a separating membrane.

[0015] This application utilizes raw materials including porous cellulose particles to obtain a slurry, which can then be directly used to coat the base membrane. Therefore, it is compatible with conventional separator preparation processes and easy to promote industrial application. Due to the loose, porous structure of the cellulose particles, the separator exhibits high electrolyte wettability. Furthermore, porous cellulose particles are more pressure-resistant than directly used cellulose, resulting in better porosity retention and improving the overall electrolyte retention capacity of the separator. This mitigates localized electrolyte depletion and lithium plating at corners during subsequent battery cycles, reducing the risk of sudden capacity drops. Simultaneously, compared to commonly used inorganic heat-resistant particles such as boehmite and alumina, porous cellulose particles are lighter, increasing the energy density of individual battery cells. Additionally, porous cellulose particles have better compatibility with organic materials such as binders in the coating compared to inorganic heat-resistant particles, thus facilitating the bonding effect of the binder. This allows for a reduction in the amount of binder used while achieving the same bonding effect, further improving the mass energy density of the battery cell. Alternatively, the same amount of binder can be used to improve the bonding effect between the separator and the electrode, thereby improving the cycle performance of the battery cell.

[0016] In any embodiment of the second aspect of this application, the preparation process further includes the process of preparing porous cellulose particles, the process of preparing porous cellulose particles including:

[0017] Cellulose is dissolved and dispersed to obtain a cellulose dispersion.

[0018] The cellulose dispersion was frozen and then thawed.

[0019] The thawed cellulose dispersion was dried to obtain porous cellulose particles.

[0020] In any embodiment of the second aspect of this application, the solid content of the cellulose dispersion is 5 wt% to 25 wt%.

[0021] In any embodiment of the second aspect of this application, the process of dissolving and dispersing cellulose includes:

[0022] A cellulose dispersion is formed by mixing alkali, urea, and cellulose with water. Optionally, the process of dissolving and dispersing cellulose also satisfies one or more of the following conditions:

[0023] The weight ratio of alkali, urea and cellulose is (5-15):(5-25):(1-10);

[0024] Cellulose is one or more of plant cellulose and bacterial cellulose fibers.

[0025] In any embodiment of the second aspect of this application, the process of drying the thawed cellulose dispersion to obtain porous cellulose particles includes:

[0026] The thawed cellulose dispersion was subjected to a first drying process to obtain initial cellulose particles.

[0027] The initial cellulose particles are washed with water and then subjected to a second drying process to obtain porous cellulose particles.

[0028] In any embodiment of the second aspect of this application, the first drying is spray drying.

[0029] In any embodiment of the second aspect of this application, a portion of the porous cellulose particles are replaced with inorganic heat-resistant particles.

[0030] In any embodiment of the second aspect of this application, the weight ratio of porous cellulose particles to inorganic heat-resistant particles is (10-60):(90-40), optionally 30-60:70-40.

[0031] A third aspect of this application provides an isolation membrane comprising a base membrane and a coating located on at least one side of the base membrane, wherein the coating comprises porous cellulose particles.

[0032] This application provides a coating comprising porous cellulose particles on at least one side of the base membrane. The electrolyte enters the porous structure of the cellulose particles, achieving high electrolyte absorption and wettability of the separator. Furthermore, the porous cellulose particles are more pressure-resistant than directly using cellulose, resulting in better porosity retention and improving the overall electrolyte retention capacity of the separator. This mitigates localized electrolyte depletion and lithium plating at corners during subsequent cycles, reducing the risk of sudden capacity drops and improving the cycle performance of individual battery cells. Simultaneously, compared to commonly used inorganic heat-resistant particles such as boehmite and alumina, porous cellulose particles are lighter, increasing the gravimetric energy density of the battery cells. Additionally, porous cellulose particles exhibit better compatibility with organic materials such as binders in the coating compared to inorganic heat-resistant particles, thus facilitating the bonding effect of the binder. This allows for a reduction in the amount of binder used while achieving the same bonding effect, further improving the gravimetric energy density of the battery cells. Alternatively, the same amount of binder can be used to improve the bonding effect between the separator and the electrode, thereby improving the cycle performance of the battery cells.

[0033] In any embodiment of the third aspect of this application, the porosity of the separator is 44%-53%.

[0034] In any embodiment of the third aspect of this application, the porous cellulose particles are spherical or near-spherical particles, and optionally, the sphericity of the porous cellulose particles is 0.83-0.91.

[0035] In any embodiment of the third aspect of this application, the average particle size of the porous cellulose particles is 10-16 μm.

[0036] In any embodiment of the third aspect of this application, the porous cellulose particles include any one or more of plant cellulose particles or bacterial cellulose fiber particles.

[0037] In any embodiment of the third aspect of this application, the coating further includes inorganic heat-resistant particles.

[0038] In any embodiment of the third aspect of this application, the weight ratio of porous cellulose particles to inorganic heat-resistant particles in the coating is (10-60):(90-40), optionally 30-60:70-40.

[0039] The fourth aspect of this application provides a battery device comprising a battery cell according to any embodiment of the first aspect of this application or a battery cell prepared by a preparation method according to any embodiment of the second aspect of this application.

[0040] The fifth aspect of this application provides an electrical device comprising a battery cell according to any embodiment of the first aspect of this application, a battery cell prepared by a preparation method according to any embodiment of the second aspect of this application, or a battery device according to the fourth aspect of this application. Attached Figure Description

[0041] To more clearly illustrate the technical solutions of the embodiments of this application, the drawings used in the embodiments of this application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the drawings without creative effort.

[0042] Figure 1 This is a schematic diagram of a battery cell according to one embodiment of this application.

[0043] Figure 2 yes Figure 1 An exploded view of a battery cell according to one embodiment of this application is shown.

[0044] Figure 3 This is a schematic diagram of a battery module according to one embodiment of this application.

[0045] Figure 4 This is a schematic diagram of a battery pack according to one embodiment of this application.

[0046] Figure 5 yes Figure 4 An exploded view of a battery pack according to one embodiment of this application is shown.

[0047] Figure 6 This is a schematic diagram of an electrical device in which a single battery cell is used as a power source according to one embodiment of this application.

[0048] Figure 7 This is a SEM micrograph of the porous cellulose particle raw material prepared in Example 8 of this application.

[0049] Figure 8 This is a SEM micrograph of the coating surface of the isolation membrane prepared in Example 1 of this application.

[0050] The accompanying drawings are not drawn to scale.

[0051] Explanation of reference numerals in the attached figures:

[0052] 1 Battery pack; 2 Upper housing; 3 Lower housing; 4 Battery module; 5 Battery cell; 51 Housing; 52 Electrode assembly; 53 Top cover assembly. Detailed Implementation

[0053] The embodiments of this application will be described in further detail below with reference to the accompanying drawings and examples. The detailed description of the following embodiments and the accompanying drawings are used to illustrate the principles of this application by way of example, but should not be used to limit the scope of this application, that is, this application is not limited to the described embodiments.

[0054] The following detailed description, with appropriate reference to the accompanying drawings, discloses embodiments of the separator and its preparation method, battery cell and its preparation method, secondary battery, battery module, battery pack, and power supply device of this application. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided for a full understanding of this application by those skilled in the art and are not intended to limit the subject matter of the claims.

[0055] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0056] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.

[0057] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.

[0058] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0059] Unless otherwise specified, the terms "comprising" and "including" as used in this application are open-ended. For example, "comprising" and "including" may mean that other components not listed may also be included or contained.

[0060] Unless otherwise specified, the term "or" is inclusive in this application. For example, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0061] [Isolation membrane]

[0062] Under the influence of gravity and electrode cyclic expansion stress, the electrolyte absorbed by the separator will flow and drain, resulting in electrolyte deficiency at the edges and corners of the battery cells. Poor electrolyte wetting easily leads to lithium plating at corners, which in turn causes a sharp drop in capacity during cycling. In order to improve the problems of electrolyte deficiency at the top and lithium plating at corners of the battery cells and prevent the sharp capacity decay of the battery cells, the first embodiment of this application provides a separator, including a base film and a coating located on at least one side of the base film, wherein the coating includes porous cellulose particles.

[0063] This application provides a coating comprising porous cellulose particles on at least one side of the base membrane. The electrolyte enters the porous structure of the cellulose particles, achieving high electrolyte absorption and wettability of the separator. Furthermore, the porous cellulose particles are more pressure-resistant than directly using cellulose, resulting in better porosity retention and improving the overall electrolyte retention capacity of the separator. This mitigates localized electrolyte depletion and lithium plating at corners during subsequent cycles, reducing the risk of sudden capacity drops and improving the cycle performance of individual battery cells. Simultaneously, compared to commonly used inorganic heat-resistant particles such as boehmite and alumina, porous cellulose particles are lighter, increasing the gravimetric energy density of the battery cells. Additionally, porous cellulose particles exhibit better compatibility with organic materials such as binders in the coating compared to inorganic heat-resistant particles, thus facilitating the bonding effect of the binder. This allows for a reduction in the amount of binder used while achieving the same bonding effect, further improving the gravimetric energy density of the battery cells. Alternatively, the same amount of binder can be used to improve the bonding effect between the separator and the electrode, thereby improving the cycle performance of the battery cells.

[0064] Because porous cellulose particles are used in the coating of this application, the porosity of the separator can be increased. In some embodiments, the porosity of the separator is 44%-53%. Controlling the porosity of the separator within the above range not only improves the overall liquid absorption and retention capacity of the separator but also does not degrade its heat resistance.

[0065] The porosity of the separator membrane in this application can be obtained by testing using the following methods:

[0066] Testing the porosity ε of the isolation membrane (gas displacement method): The isolation membrane with a known apparent volume V1 is crumpled into a ball and stuffed into a sample cup. The sample cup containing the sample is placed in a true density tester, the test system is sealed, and helium gas is introduced according to the procedure. By detecting the gas pressure in the sample chamber and the expansion chamber, the true volume V2 is calculated according to Bohr's law (PV=nRT). ε=(V1-V2) / V1*100%, where V1 is the apparent volume of the sample and V2 is the true volume of the sample.

[0067] In some embodiments, the porous cellulose particles are spherical or near-spherical particles. Optionally, the sphericity of the porous cellulose particles is 0.83-0.91. Spherical or near-spherical particles with sphericity within the above range can form a more uniform overlap and dispersion in the coating, which is beneficial to the full utilization of its pore structure, thereby improving the overall liquid absorption and retention capacity of the separator membrane.

[0068] The sphericity of the porous cellulose particles in the coating of the separator membrane of this application can be estimated based on a two-dimensional sphericity formula derived from a projected image of the porous cellulose particles obtained by resolution of the coating, followed by centrifugation and drying.

[0069] 1. Roundness: Using SEM microscopic images, two-dimensional projections of particles are obtained through image processing software (such as ImageJ and Fiji), and the projected area and perimeter of each particle are automatically measured. The roundness value is calculated to characterize the sphericity, with the value closer to 1 indicating that it is closer to a sphere.

[0070] 2. Aspect Ratio: Using SEM microscopic images, two-dimensional projections of particles are obtained through image processing software (such as ImageJ and Fiji), and the lengths of the longest axis (major axis) and the minor axis perpendicular to it are measured. The aspect ratio is used to characterize sphericity; the closer the aspect ratio is to 1, the closer the shape is to spherical.

[0071] The above microscopic images were obtained using the following method: After resolvating the coating (the solvent that can dissolve the binder and dispersant in the coating can be selected based on the specific substances of the binder and dispersant and the principle of chemical dissolution, such as water, a solvent commonly used in the preparation of coating slurries), the binder and dispersant were removed by repeated washing, and the porous cellulose particles and inorganic heat-resistant particles were separated by centrifugation. For example, in one exemplary method, the coated separator (if it is a separator removed from a battery, it needs to be cleaned with DMC to remove lithium salts first) was immersed in water to thoroughly wash away the coating. The resulting aqueous dispersion of the coating was centrifuged at 1200 rpm for 1 minute, and the supernatant was temporarily stored. The centrifugation was repeated three times with the addition of water. Finally, the centrifuged precipitate was separated, with the upper layer being porous cellulose particles and the lower layer being inorganic heat-resistant particles. The separated porous cellulose particles were dried for SEM characterization.

[0072] In some embodiments, the average particle size of the porous cellulose particles is 10-16 μm. When the average particle size of the porous cellulose particles is within the above range, they are less prone to agglomeration, which is beneficial for their dispersion in the binder, thereby improving the adhesion between the coating and the base film, and between the coating and the electrode. At the same time, the stacking between the particles can increase the porosity between the particles, further improving the overall liquid absorption and retention capacity of the separator.

[0073] The average particle size of the porous cellulose particles in the coating of the separator membrane of this application can be obtained by the following method:

[0074] A 3.6 mm × 3.6 mm sample is cut from any region of the separator. The microstructure of the coating in the sample is plotted using a scanning electron microscope (e.g., ZEISS Sigma 300). The high vacuum mode is selected, the working voltage is 3 kV, and the magnification is 30,000 times to obtain the SEM image. Based on the obtained SEM image, multiple (e.g., more than 5, exemplarily 10 or 15) test areas are selected to statistically analyze the particle size. The average particle size obtained from each test area is then taken as the average particle size of the porous cellulose particles.

[0075] In some embodiments of this application, the porous cellulose particles include any one or more of plant cellulose particles or bacterial cellulose fiber particles. Bacterial cellulose has higher porosity and higher strength than plant cellulose, and can be selected from it according to the need to improve the cycle performance of the battery cell in the application; this application does not specifically limit it.

[0076] In some embodiments of this application, the coating further includes inorganic heat-resistant particles. Optionally, the inorganic heat-resistant particles include at least one selected from boehmite, alumina, barium sulfate, magnesium oxide, magnesium hydroxide, silicon oxide, tin dioxide, titanium oxide, calcium oxide, zinc oxide, zirconium oxide, yttrium oxide, nickel oxide, hafnium dioxide, cerium oxide, zirconium titanate, barium titanate, and magnesium fluoride. More preferably, the inorganic particles include at least one selected from boehmite, alumina, barium sulfate, magnesium oxide, silicon oxide, titanium oxide, zinc oxide, cerium oxide, and barium titanate. By introducing inorganic heat-resistant particles into the coating, the heat resistance of the separator can be improved. Moreover, the hardness of inorganic heat-resistant particles is greater than that of porous cellulose particles, thus better resisting the compression of the separator caused by the volume expansion of the electrode during battery cell cycling. This provides a stable physical space for the liquid retention capacity of the porous cellulose particles, allowing their liquid retention effect to be more fully realized.

[0077] In some embodiments of this application, the weight ratio of porous cellulose particles to inorganic heat-resistant particles in the coating is (10-60):(90-40), optionally (30-60):(70-40). Controlling the weight ratio of porous cellulose particles to inorganic heat-resistant particles within this range improves the heat resistance of the separator without compromising its liquid absorption and retention properties. Simultaneously, the inorganic heat-resistant particles dilute the porous cellulose particles, improving their dispersion uniformity in the coating and reducing the viscosity of the slurry used to form the coating, thus facilitating slurry application.

[0078] The weight ratio of porous cellulose particles to inorganic heat-resistant particles in the coating of this application can be obtained by testing using the following methods:

[0079] After resolvating the coating (choosing a solvent that can dissolve the binder and dispersant in the coating based on the specific substances of the binder and dispersant and the principle of chemical dissolution, such as water, a commonly used solvent for preparing coating slurries), wash repeatedly to remove the binder and dispersant. Centrifuge to separate porous cellulose particles and inorganic heat-resistant particles, then dry and weigh to calculate the weight ratio. For example, in one example method, the coated separator (if it is a separator removed from a battery, it needs to be cleaned with DMC to remove lithium salts first) is immersed in water to thoroughly wash away the coating. The resulting aqueous dispersion of the coating is centrifuged at 1200 rpm for 1 minute, and the upper layer is temporarily stored. Repeat the centrifugation with water, and temporarily store the solution three times. Finally, separate the centrifuged precipitate, where the upper layer is porous cellulose particles and the lower layer is inorganic heat-resistant particles. Dry and weigh, and dry and weigh the temporarily stored solution to obtain the weight of porous cellulose particles, the weight of inorganic heat-resistant particles, and the weight of binder / dispersant, thus obtaining the weight ratio of porous cellulose particles to inorganic heat-resistant particles.

[0080] In some embodiments, the coating also includes a binder, and optionally a dispersant. This application does not have particular requirements for the binder and dispersant; both fluorinated and non-fluorinated binders can be used, and will not be elaborated further here.

[0081] In some embodiments of this application, the base film is a polyethylene separator film, a polypropylene separator film, or a polyethylene / polypropylene / polyethylene composite separator film.

[0082] In some embodiments, the coating includes a heat-resistant coating and an adhesive layer, the heat-resistant coating being disposed between the base film and the adhesive layer, and the porous cellulose particles and optional inorganic heat-resistant particles being disposed within the heat-resistant coating.

[0083] In some embodiments, the above coating is a heat-resistant adhesive coating, that is, the heat resistance function and the adhesive function are combined in one coating. The adhesive, dispersant and other components can be referenced from the commonly used materials of conventional heat-resistant adhesive coatings, and will not be described in detail here.

[0084] The second embodiment of this application provides a method for preparing a separator membrane, comprising: mixing raw materials including porous cellulose particles, a dispersant and a binder to obtain a slurry; and placing the slurry on at least one side of a base membrane and drying it to obtain a separator membrane.

[0085] This application utilizes raw materials including porous cellulose particles to obtain a slurry, which can then be directly used to coat the base membrane. Therefore, it is compatible with conventional separator preparation processes and easy to promote industrial application. Due to the loose, porous structure of the cellulose particles, the separator exhibits high electrolyte wettability. Furthermore, porous cellulose particles are more pressure-resistant than directly used cellulose, resulting in better porosity retention and improving the overall electrolyte retention capacity of the separator. This mitigates localized electrolyte depletion and lithium plating at corners during subsequent battery cycles, reducing the risk of sudden capacity drops. Simultaneously, compared to commonly used inorganic heat-resistant particles such as boehmite and alumina, porous cellulose particles are lighter, increasing the energy density of individual battery cells. Additionally, porous cellulose particles have better compatibility with organic materials such as binders in the coating compared to inorganic heat-resistant particles, thus facilitating the bonding effect of the binder. This allows for a reduction in the amount of binder used while achieving the same bonding effect, further improving the mass energy density of the battery cell. Alternatively, the same amount of binder can be used to improve the bonding effect between the separator and the electrode, thereby improving the cycle performance of the battery cell.

[0086] In some embodiments of this application, the preparation process further includes the preparation of porous cellulose particles. The preparation of porous cellulose particles includes: dissolving and dispersing cellulose to obtain a cellulose dispersion; freezing the cellulose dispersion and then thawing it; and drying the thawed cellulose dispersion to obtain porous cellulose particles.

[0087] The freezing process significantly improves dissolution efficiency and porosity by physically disrupting the crystalline structure of cellulose and enhancing solvent permeability, as detailed below:

[0088] When cellulose is mixed with a solvent and then frozen, the water in the solvent (such as NaOH / urea solution) expands in volume as it freezes, and the resulting mechanical stress can disrupt the crystalline regions of cellulose. Some solvents (such as the alkali / urea system) have stronger dissolving power at low temperatures (such as -12°C). For example, at low temperatures, urea and NaOH form a hydrogen bond network that encapsulates the cellulose molecular chains, weakening their intermolecular forces. Furthermore, repeated freezing and thawing can increase the solvent contact area and expand the porosity of cellulose.

[0089] Therefore, by successively freezing, thawing, and drying cellulose that has undergone dissolution and dispersion treatment to obtain porous cellulose particles, the pore structure of the cellulose particles can be increased.

[0090] In some embodiments of this application, the solid content of the cellulose dispersion is 5 wt% to 25 wt%. Controlling the solid content of the cellulose dispersion facilitates the thorough dispersion of cellulose by the solvent, provides a better liquid filling basis for the freezing process, and thus achieves a higher sphericity of the cellulose particles.

[0091] The formation of a cellulose dispersion can refer to various conventional physical or chemical methods for dissolving and dispersing cellulose. To avoid the formation of porous cellulose particles with residual formulations affecting the performance of the battery cells, in some embodiments of this application, the process of dissolving and dispersing cellulose includes: mixing alkali, urea, and cellulose with water to form a cellulose dispersion. Urea is volatile in water, therefore it is less likely to remain in the cellulose particles and is beneficial for the formation of pores in the cellulose particles; alkali is easily eluted and is also less likely to remain. Simultaneously, using an alkali / urea system to dissolve cellulose facilitates the formation of more pores during the subsequent freezing process.

[0092] In some embodiments, the process of dissolving and dispersing cellulose also satisfies one or more of the following conditions: the weight ratio of alkali, urea and cellulose is (5-15):(5-25):(1-10); the alkali is one or more of alkali metal hydroxides and alkaline earth metal hydroxides, optionally one or more of sodium hydroxide, lithium hydroxide, potassium hydroxide and calcium hydroxide; and the cellulose is one or more of plant cellulose and bacterial cellulose fibers.

[0093] The alkali / urea system can dissolve cellulose, and the dissolution of cellulose can be maximized by controlling the weight ratio of alkali, urea and cellulose.

[0094] In some embodiments of this application, the cellulose dispersion is frozen at -12°C to 0°C and kept at that temperature for 24 to 72 hours, then thawed at 20°C to 30°C. Freezing temperature, holding time, and thawing temperature within this range can improve the dissolution effect of cellulose, which is beneficial for forming cellulose particles with high porosity and uniform particle size, thereby improving the overall liquid absorption and retention capacity of the separator membrane.

[0095] The thawed cellulose dispersion is dried to remove the liquid, forming abundant pores. In some embodiments of this application, the process of drying the thawed cellulose dispersion to obtain porous cellulose particles includes: subjecting the thawed cellulose dispersion to a first drying to obtain initial cellulose particles; washing the initial cellulose particles with water and then performing a second drying to obtain porous cellulose particles. Washing the initial cellulose particles with water can remove residual urea and alkali from the cellulose particles, thereby further increasing the porosity of the cellulose particles and removing residual impurities.

[0096] In some embodiments of this application, the first drying is spray drying. In some embodiments, spray drying satisfies any one or more of the following conditions:

[0097] Inlet temperature: 150℃-300℃; outlet temperature: 60℃-150℃; spray pressure: 2bar-4bar; feed flow rate: 1000mL / h-2000mL / h.

[0098] Compared with other drying methods, spray drying can produce spherical or near-spherical cellulose particles, which have a more uniform and higher porosity than non-spherical cellulose particles, thereby improving the overall liquid absorption and retention capacity of the separator membrane.

[0099] For example, the sphericity of the formed porous cellulose particles is 0.83-0.91, the average particle size is 10μm-16μm, the porosity is 51%-69%, and the pore size is 2nm-50nm.

[0100] In some embodiments of this application, the weight ratio of porous cellulose particles, dispersant, and binder is (80-95):(1-7):(4-13), and / or the solid content of the slurry is 8wt% to 45wt%. Controlling the proportion of porous cellulose particles, dispersant, and binder in the slurry and the solid content of the slurry can improve the distribution of porous cellulose particles in the coating and enhance the adhesion of the coating.

[0101] In some embodiments of this application, a portion of the porous cellulose particles are replaced with inorganic heat-resistant particles. Optionally, the inorganic heat-resistant particles include at least one selected from boehmite, alumina, barium sulfate, magnesium oxide, magnesium hydroxide, silicon oxide, tin dioxide, titanium oxide, calcium oxide, zinc oxide, zirconium oxide, yttrium oxide, nickel oxide, hafnium dioxide, cerium oxide, zirconium titanate, barium titanate, and magnesium fluoride. More preferably, the inorganic heat-resistant particles include at least one selected from boehmite, alumina, barium sulfate, magnesium oxide, silicon oxide, titanium oxide, zinc oxide, cerium oxide, and barium titanate. By introducing inorganic heat-resistant particles into the coating, the heat resistance of the separator can be improved.

[0102] In some embodiments of this application, the weight ratio of porous cellulose particles to inorganic heat-resistant particles is (10-60):(90-40), optionally (30-60):(70-40). Controlling the weight ratio of porous cellulose particles to inorganic heat-resistant particles in the coating within the above range can improve the heat resistance of the separator without compromising its liquid absorption and retention properties. Simultaneously, the inorganic heat-resistant particles dilute the porous cellulose particles, improving their dispersion uniformity in the coating and reducing the viscosity of the slurry forming the coating, thus facilitating slurry application.

[0103] In any embodiment of the second aspect of this application, the base film is a polyethylene separator film, a polypropylene separator film, or a polyethylene / polypropylene / polyethylene composite separator film.

[0104] [Battery cell]

[0105] A single battery cell can be a rechargeable battery. A rechargeable battery is a battery cell that can be recharged after it has been discharged, allowing the active materials to be activated and the cell to continue to be used.

[0106] The battery cell can be a lithium-ion battery, sodium-ion battery, sodium-lithium-ion battery, lithium metal battery, lithium-sulfur battery, magnesium-ion battery, nickel-metal hydride battery, nickel-cadmium battery, lead-acid battery, etc., and the embodiments of this application are not limited to this.

[0107] The third embodiment of this application provides a battery cell including a positive electrode, a negative electrode, and a separator located between the positive electrode and the negative electrode, wherein the separator includes any of the separators provided in the first embodiment described above.

[0108] The fourth embodiment of this application provides a method for preparing a battery cell, including any of the methods for preparing a separator provided in the second embodiment above.

[0109] [Positive electrode plate]

[0110] In some embodiments, the positive electrode can be a positive electrode sheet, which may include a positive current collector and a positive active material disposed on at least one surface of the positive current collector.

[0111] As an example, the positive current collector has two surfaces opposite each other in its own thickness direction, and the positive active material is disposed on either or both of the two opposite surfaces of the positive current collector.

[0112] As an example, the positive current collector can be a metal foil, a conductive polymer material, a carbon material, or a composite current collector. For example, as a metal foil, pure metals, alloys, or surface-treated metals can be used, including but not limited to stainless steel, copper, aluminum, nickel, titanium, or silver. The composite current collector may include a polymer material base layer and a metal layer. The composite current collector can be formed by forming a metal material (aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys, etc.) on a polymer material substrate (such as a substrate of polypropylene, polyethylene terephthalate, polybutylene terephthalate, polystyrene, polyethylene, etc.).

[0113] In some embodiments, the battery cell is a lithium-ion battery, and the positive electrode active material can be a positive electrode active material known in the art for lithium-ion batteries. The positive electrode active material may include at least one of the following materials: lithium phosphate, lithium transition metal oxide, and their respective modified compounds. However, this application is not limited to these materials, and other conventional materials that can be used as battery positive electrode active materials may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium phosphate include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4, also referred to as LFP), lithium iron phosphate and carbon composites, lithium manganese phosphate (such as LiMnPO4), lithium manganese phosphate and carbon composites, lithium iron manganese phosphate, and lithium iron manganese phosphate and carbon composites. Examples of lithium transition metal oxides include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, and lithium nickel cobalt manganese oxide (such as LiNi). 1 / 3 Co 1 / 3Mn 1 / 3 O2, also known as NCM333 or LiNi 0.5 Co 0.2 Mn 0.3 O2, also known as NCM523 or LiNi 0.5 Co 0.25 Mn 0.25 O2, also known as NCM211 or LiNi 0.6 Co 0.2 Mn 0.2 O2, also known as NCM622 or LiNi 0.8 Co 0.1 Mn 0.1 O2, also known as NCM811), lithium nickel cobalt aluminum oxide (such as LiNi) 0.85 Co 0.05 Al 0.05 At least one of O2 and its modified compounds. Modified compounds refer to substances obtained by modification methods such as doping or coating based on the above-mentioned substances.

[0114] In some embodiments, the battery cell is a sodium-ion battery, and the positive electrode active material can be a positive electrode active material known in the art for use in sodium-ion batteries. As an example, the positive electrode active material may include sodium transition metal oxides, polyanionic compounds, Prussian blue compounds, etc., and other conventionally known materials that can be used as positive electrode active materials for sodium-ion batteries can also be used. For example, as an optional technical solution in this application, in the sodium transition metal oxide, the transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce. The sodium transition metal oxide is, for example, NaxMO2, where M is one or more of Ti, V, Mn, Co, Ni, Fe, Cr, and Cu, and 0 <x≤1。

[0115] As an optional technical approach in this application, the polyanionic compound can be a compound containing sodium ions, transition metal ions, or a tetrahedral (YO4) structure. n- A class of compounds with anionic units. The transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce; Y can be at least one of P, S, and Si; n represents (YO4). n- The valence state. Polyanionic compounds can also have sodium ions, transition metal ions, or tetrahedral (YO4) ions. n- A class of compounds containing anionic units and halide anions. The transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce; Y can be at least one of P, S, and Si, and n represents (YO4). n- The valence state; the halogen can be at least one of F, Cl, and Br. Polyanionic compounds can also have sodium ions, tetrahedral (YO4) valence states. n- Anionic unit, polyhedral unit (ZO) y ) m+ And a class of compounds with optional halide anions. Y can be at least one of P, S, and Si, and n represents (YO4). n- The valence state; Z represents a transition metal, which can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce; m represents (ZO) y ) m+ The valence state; the halogen can be at least one of F, Cl, and Br. Examples of polyanionic compounds include NaFePO4, Na3V2(PO4)3 (sodium vanadium phosphate, abbreviated as NVP), Na4Fe3(PO4)2 (P2O7), NaM'PO4F (M' is one or more of V, Fe, Mn, and Ni), and Na3(VO4)2. y )2(PO4)2F 3-2y At least one of (0≤y≤1).

[0116] As an optional technical solution of the present application, the polyanionic compound may be Na x-a A a V y-b M b (PO4) 2-2c (DO4) 2c F z-d Q d , where element A represents an alkali metal element doped to substitute for the Na element, element M represents a metal element substituting for the V element, element D represents a doping element substituting for the P element, element Q represents a doping element substituting for the F element, the element D includes at least one of Si and S, and the element Q includes at least one of Cl and O; 3.5≤x≤4.5, 0≤a≤0.15x, 0.8≤y≤1.1, 0≤b≤0.3y, 0≤c≤0.15, 0.8≤z≤1.1, 0≤d≤0.2z. Optionally, the element A includes at least one of K and Li; the element M includes at least one of Fe, Cr, Al, Sc, Ga, In, Ti, Zr, Mn, Zn, Ni, Cu and Co.

[0117] As an optional technical solution of the present application, the polyanionic compound may be Na x R y (PO4)2P2O7, where x=3.5-4.5, y=2.75-3.25, and R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Cr, Nb, Mo, In, Ga, Sn, Hf, Ta, W and Pb.

[0118] As an optional technical solution of the present application, the polyanionic compound may be Na4+xR 3-y P 4-m O 15 / C; where 0<x<0.5, 0<y≤0.5, 0<m≤0.2, and R includes at least one of Mg, Al, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Zr, Cr, Nb, Mo, In, Ga, Sn, Hf, Ta, W and Pb.

[0119] The Prussian blue analog compound may be a type of compound having sodium ions, transition metal ions and cyanide ions (CN-). The transition metal may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce. Examples of the Prussian blue analog compound are Na a Me b Me’ c(CN)6, wherein Me and Me' are each independently at least one of Ni, Cu, Fe, Mn, Co, and Zn, 0 <a≤2,0<b<1,0<c<1。

[0120] In some embodiments, the positive electrode active material includes at least one of sodium-containing layered oxides, polyanionic sodium compounds, and Prussian blue sodium compounds.

[0121] In some embodiments, the sodium-containing layered oxide is an iron-manganese layered oxide, specifically including at least one of nickel-iron-manganese layered oxide and copper-iron-manganese layered oxide.

[0122] During the charging and discharging process, active ions (Na+) are intercalated and deintercalated, resulting in a different molar content of Na at different discharge states. In the examples of positive electrode active materials in this application, the molar content of Na refers to the initial state of the material, i.e., the state before feeding. When the positive electrode active material is applied to the battery system, the molar content of Na changes after charge-discharge cycles.

[0123] In the examples of positive electrode active materials in this application, the molar content of oxygen is only a theoretical value. Oxygen release from the crystal lattice will cause changes in the molar content of oxygen, and the actual molar content of oxygen will fluctuate.

[0124] In some embodiments, the positive electrode film layer may optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.

[0125] In some embodiments, the positive electrode film may optionally include a conductive agent. As an example, the conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0126] In some embodiments, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet, such as positive active material, conductive agent, binder and any other components, in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry onto the positive electrode current collector, and then obtaining the positive electrode sheet after drying, cold pressing and other processes.

[0127] [Negative electrode plate]

[0128] The negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector, the negative electrode film layer including a negative electrode active material.

[0129] As an example, the negative electrode current collector has two surfaces opposite each other in its own thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.

[0130] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0131] In some embodiments, the negative electrode active material may be a negative electrode active material known in the art for use in batteries. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate, etc. Silicon-based materials may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Tin-based materials may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, this application is not limited to these materials, and other conventional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0132] In some embodiments, the negative electrode film layer may optionally include a binder. As an example, the binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0133] In some embodiments, the negative electrode film may optionally include a conductive agent. As an example, the conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0134] In some embodiments, the negative electrode film may optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).

[0135] In some embodiments, the negative electrode sheet can be prepared by dispersing the components used to prepare the negative electrode sheet, such as the negative electrode active material, conductive agent, binder and any other components, in a solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto the negative electrode current collector, and then obtaining the negative electrode sheet after drying, cold pressing and other processes.

[0136] [Electrolytes]

[0137] The electrolyte acts as a conductor of ions between the positive and negative electrodes. This application does not impose specific restrictions on the type of electrolyte; it can be selected according to requirements. For example, the electrolyte can be liquid, gel, or entirely solid.

[0138] In some embodiments, the electrolyte is liquid and includes an electrolyte salt and a solvent.

[0139] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate.

[0140] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.

[0141] In some embodiments, the electrolyte may optionally include additives. As examples, additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc.

[0142] In some implementations, the positive electrode, negative electrode, and separator can be fabricated into an electrode assembly using a winding or stacking process.

[0143] In some implementations, the secondary battery includes a single secondary battery cell, or a battery module and a battery pack.

[0144] In some embodiments, the secondary battery may include an outer packaging. This outer packaging may be used to encapsulate the aforementioned electrode assembly and electrolyte.

[0145] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. The outer packaging of the secondary battery can also be a soft pack, such as a pouch. The material of the soft pack can be plastic; examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0146] This application does not impose any particular limitation on the shape of the secondary battery cell; it can be cylindrical, square, or any other arbitrary shape. For example, Figure 1 The example shown is a square-structured secondary battery cell 5.

[0147] In some implementations, refer to Figure 2 The outer packaging may include a housing 51 and a top cover assembly 53. The housing 51 may include a base plate and side plates connected to the base plate, the base plate and side plates forming a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the top cover assembly 53 can cover the opening to close the receiving cavity. The positive electrode sheet, negative electrode sheet, and separator can be formed into an electrode assembly 52 by a winding process or a stacking process. The electrode assembly 52 is encapsulated within the receiving cavity. Electrolyte is immersed in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery cell 5 can be one or more, which can be selected by those skilled in the art according to specific practical needs.

[0148] In some implementations, the secondary battery cells can be assembled into a battery module. The number of secondary battery cells contained in the battery module can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery module.

[0149] Figure 3 This is battery module 4, used as an example. (See reference...) Figure 3 In battery module 4, multiple secondary battery cells 5 can be arranged sequentially along the length of battery module 4. Of course, they can also be arranged in any other manner. Furthermore, these multiple secondary battery cells 5 can be fixed in place using fasteners.

[0150] Optionally, the battery module 4 may also include a housing with a receiving space in which multiple secondary battery cells 5 are received.

[0151] In some embodiments, the battery modules described above can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be one or more, the specific number of which can be selected by those skilled in the art according to the application and capacity of the battery pack.

[0152] Figure 4 and Figure 5 This is battery pack 1 as an example. (See reference...) Figure 4 and Figure 5The battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box includes an upper body 2 and a lower body 3, with the upper body 2 covering the lower body 3 to form a closed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.

[0153] In addition, this application also provides an electrical device, which includes the secondary battery provided in this application. The secondary battery can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0154] As the electrical device, a single secondary battery cell, a battery module, or a battery pack can be selected according to its usage requirements.

[0155] Figure 6 This is an example of an electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery for this device, a battery pack or battery module can be used.

[0156] [Example]

[0157] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.

[0158] Example 1

[0159] Preparation of porous cellulose particles:

[0160] Sodium hydroxide, urea, and plant cellulose (obtained from bamboo fiber) were mixed with water in a weight ratio of 7:12:1 to form a cellulose dispersion with a solid content of 20 wt%. The cellulose dispersion was then frozen at -12°C and held at that temperature for 24 hours, followed by thawing at 25°C. The thawed cellulose dispersion was then spray-dried (inlet temperature 200°C; outlet temperature 80°C; spray pressure 2.5 bar; feed flow rate: 1200 mL / h) to obtain initial cellulose particles. The initial cellulose particles were then washed with water and dried again to obtain porous cellulose particles. The average particle size of the porous cellulose particles was measured to be 13 micrometers using a laser particle size analyzer. The sphericity of the porous cellulose particles was determined using a two-dimensional sphericity formula based on a projected image. Estimation: Using SEM microscopic images and image processing software (such as ImageJ, Fiji), the two-dimensional projection of the particles was obtained, and the projected area and perimeter of each particle were automatically measured. The roundness value was calculated to be 0.91.

[0161] Preparation of the separating membrane:

[0162] A slurry containing porous cellulose particles, a dispersant (carboxymethyl cellulose), and a binder (acrylate) in a weight ratio of 94:2:4 was mixed to obtain a slurry with a solid content of 23 wt%. The slurry was then applied to at least one side of a base membrane (polyethylene membrane, 6 μm thick) and dried to obtain a release membrane with a coating thickness of 18 μm.

[0163] Positive electrode preparation:

[0164] LiNi, the positive electrode active material 0.8 Co 0.1 Mn 0.1 O2 is thoroughly mixed with binder PVDF and N-methylpyrrolidone to form a uniform and transparent adhesive solution. Positive electrode conductive agent SP carbon black is added to the adhesive solution and stirred thoroughly. After mixing evenly, the slurry is sieved and then coated onto the positive electrode current collector (Al foil). After rolling and slitting, the positive electrode sheet is obtained for later use. The weight ratio of positive electrode active material (NCM811), binder (PVDF), and conductive agent (SP carbon black) in the positive electrode slurry is 96:2:2.

[0165] Negative electrode preparation:

[0166] The negative electrode active material is uniformly dispersed in an aqueous solution using a dispersant. The negative electrode conductive agent and the coated active material are pre-mixed and added to the aqueous solution. After stirring, the negative electrode binder is added, and the mixture is thoroughly stirred and sieved. The slurry is then coated onto a negative electrode current collector (Cu foil) according to the appropriate coating weight. The resulting electrode sheet is then rolled and slit to obtain the negative electrode sheet for later use. The negative electrode slurry contains negative electrode active material (graphite), binder (styrene-butadiene rubber), dispersant (carboxymethyl cellulose), and conductive agent (conductive carbon black) in a ratio of 96:2:1:1.

[0167] Preparation of secondary batteries:

[0168] The separator, positive electrode, and negative electrode are assembled into an electrode assembly by stacking or winding. Then, the assembly undergoes top-side sealing, high-temperature baking, liquid injection, formation, liquid injection again, and capacity testing to produce a secondary battery.

[0169] Characterization of the separating membrane:

[0170] The porosity of the membrane was determined to be 53% by gas adsorption methods (such as the BET method). Figure 8 An SEM image of the surface of the isolation membrane coating of Example 1 is shown, from which it can be clearly seen that the cellulose particles in the coating surface are porous.

[0171] The average particle size of the porous cellulose particles in the coating of the separator membrane can be obtained by the following method:

[0172] A 3.6 mm × 3.6 mm sample was cut from a randomly selected area of ​​the separator membrane. The microstructure of the coating in the sample was mapped using a scanning electron microscope (e.g., ZEISS Sigma 300). A high vacuum mode was selected, with an operating voltage of 3 kV and a magnification of 30,000x to obtain a SEM image. Based on the obtained SEM image, multiple test areas (e.g., more than 5, exemplarily 10 or 15) were selected for particle size analysis. The average particle size obtained from each test area was then taken as the average particle size of the porous cellulose particles. SEM testing showed that the average particle size of the porous cellulose particles in the separator membrane of Example 1 was 13 μm.

[0173] The sphericity of the porous cellulose particles in the coating of the separator can be determined based on a two-dimensional sphericity formula derived from a projected image of the porous cellulose particles obtained by resolution of the coating, followed by centrifugation and drying. Estimation: Using SEM microscopic images, the two-dimensional projection of the particles was obtained through image processing software (such as ImageJ, Fiji), and the projected area and perimeter of each particle were automatically measured. The roundness value was calculated to be 0.89.

[0174] The above microscopic images were obtained using the following method: After resolvating the coating (the solvent that can dissolve the binder and dispersant in the coating can be selected based on the specific substances of the binder and dispersant and the principle of chemical dissolution, such as water, a solvent commonly used in the preparation of coating slurries), the binder and dispersant were removed by repeated washing, and the porous cellulose particles and inorganic heat-resistant particles were separated by centrifugation. For example, in one exemplary method, the coated separator (if it is a separator removed from a battery, it needs to be cleaned with DMC to remove lithium salts first) was immersed in water to thoroughly wash away the coating. The resulting aqueous dispersion of the coating was centrifuged at 1200 rpm for 1 minute, and the supernatant was temporarily stored. The centrifugation was repeated three times with the addition of water. Finally, the centrifuged precipitate was separated, with the upper layer being porous cellulose particles and the lower layer being inorganic heat-resistant particles. The separated porous cellulose particles were dried for SEM characterization.

[0175] Testing of the separator membrane

[0176] Liquid absorption rate: Weigh the initial weight of the separator and record it as N1; immerse the separator in the electrolyte (electrolyte solvent is EC / DMC / EMC (volume ratio is 1:1:1), solute is 1mol / L LiPF6) for 24h, let it stand until the electrolyte on its surface evaporates, and test its mass after liquid absorption as N2. The liquid absorption rate is (N2-N1) / N1*100%.

[0177] Liquid retention rate: The initial weight of the separator is recorded as N1. After being fully immersed in the electrolyte and centrifuged at 8000 rpm, the mass of electrolyte lost by the separator during centrifugation is N2. The liquid retention rate is (N2-N1) / N1*100%.

[0178] Heat shrinkage of the release liner: Cut the release liner into three 5cm (TD) × 10cm (MD) samples, place them in a 130℃ oven for 1 hour to allow them to shrink freely, then measure the length of the three samples in the TD direction and calculate the average value as T1, and measure the length of the three samples in the MD direction and calculate the average value as M1. The formulas for calculating the shrinkage rate of the release liner in the MD and TD directions are as follows:

[0179] MD: Sm = (10 - M1) / 10 × 100%

[0180] TD: St=(5-T1) / 5×100%

[0181] According to the test results, the liquid absorption rate, liquid retention rate, and shrinkage rates in the MD and TD directions of the isolation membrane prepared in Example 1 were 39%, 36%, 2.30%, and 4.05%, respectively.

[0182] Battery performance testing

[0183] To test the battery's cycle count at 45℃ with a 10% degradation, follow these steps:

[0184] Cyclic performance test: After the battery cell is left to stand at 45℃ for 4 hours, it is charged at a 1 / 3C rate to 4.25V, then charged at a constant voltage to 0.05C, and left to stand for 0.5 hours; then discharged at a 1 / 3C rate to 2.8V, and left to stand for half an hour. The reversible capacity is measured as C1. The above charging and discharging parameters are repeatedly applied, and the discharge capacity C2 is recorded after n cycles. The capacity retention rate after the nth cycle is calculated as (C2 / C1) × 100%. This process continues until the capacity retention rate is ≤90%.

[0185] Tests showed that the battery in Example 1 did not exhibit a sharp decrease in capacity during long-cycle testing at 45°C, and the cycle capacity curve conformed to the normal lifespan degradation trend of the battery.

[0186] Examples 2-5 and Comparative Example 1

[0187] The difference between Examples 2-5 and Example 1 lies in obtaining porous cellulose granule raw materials with different sphericity, particle size, and porosity by adjusting the solid content of the cellulose dispersion and the spray pressure and feed flow rate during spray drying, as detailed in Table 1. The characterization and performance test data of the separating membrane are shown in Table 2.

[0188] Comparative Example 1

[0189] The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 directly used the cellulose dispersion prepared in Example 1 to formulate the coating slurry. Specifically, sodium hydroxide, urea, and plant cellulose were mixed with water in a weight ratio of 7:12:1 to form a cellulose dispersion with a solid content of 20 wt%. The cellulose dispersion was then frozen at -12°C and kept at that temperature for 24 hours, followed by thawing at 25°C. The raw materials containing the cellulose dispersion, dispersant (carboxymethyl cellulose), and binder (acrylate) in a weight ratio of 94:2:4 were mixed to obtain a slurry with a solid content of 23 wt%. This slurry was then applied to at least one side of a base film (polyethylene film) and dried to obtain a release film with a coating thickness of 6 μm. The characterization and performance test data of the release film are shown in Table 3.

[0190] Table 1

[0191]

[0192] Table 2

[0193]

[0194]

[0195] Table 3

[0196]

[0197] As shown in Table 1, with the same solid content in the cellulose dispersion and the same feed flow rate in spray drying, the average particle size and porosity of the porous cellulose particles decreased with increasing spray pressure, while the sphericity changed very little. Furthermore, the sphericity of the porous cellulose particles increased with increasing solid content, reaching a maximum at 20% solid content, and showed little change with further increases in solid content.

[0198] The comparison of the results of Example 1 in Table 2 and Comparative Example 1 in Table 3 shows that the separator prepared by using a coating containing porous cellulose particles has high liquid absorption and retention rates, low shrinkage rates in the MD and TD directions, and good cycle performance of the final battery. Furthermore, the results of Examples 1-6 in Table 2 further demonstrate that when the porous cellulose particles in the coating are spherical or near-spherical particles, the separator has higher liquid absorption and retention rates, lower shrinkage rates in the MD and TD directions, and better cycle performance of the final battery.

[0199] Examples 7-8

[0200] Example 7 differs from Example 1 in that it uses different cellulose raw materials, while Example 8 differs from Example 1 in that it uses different alkalis, as detailed in Table 4. The characterization and performance test data of the separator are shown in Table 5.

[0201] Table 4

[0202]

[0203] Table 5

[0204]

[0205] The results in Table 4-5 show that, compared to plant cellulose, the sphericity of porous cellulose particles decreases when the cellulose source material is bacterial cellulose. Consequently, the liquid absorption rate of the separator decreases slightly while the liquid retention rate increases slightly, the shrinkage rate in both the MD and TD directions decreases, and the cycle performance of the final battery is slightly reduced. Furthermore, compared to sodium hydroxide, when the alkali is lithium hydroxide, the liquid absorption rate and liquid retention rate of the separator decrease slightly, the shrinkage rate in both the MD and TD directions decreases, and the cycle performance of the final battery is slightly improved.

[0206] Examples 9-12

[0207] The difference between Examples 9-11 and Example 1 is that boehmite particles (i.e., inorganic heat-resistant particles) were used to replace a portion of the porous cellulose particles in the preparation of the coating slurry. The difference between Example 12 and Example 8 is that alumina particles (i.e., inorganic heat-resistant particles) were used to replace a portion of the porous cellulose particles in the same weight ratio, as detailed in Table 6. The characterization and performance test data of the separating membrane are shown in Table 7.

[0208] Table 6

[0209] Inorganic heat-resistant particles The weight ratio of porous cellulose particles to inorganic heat-resistant particles Example 1 none / Example 9 Boehmite (average grain size = 827 nm) 60:40 Example 10 Boehmite (average grain size = 827 nm) 30:70 Example 11 Boehmite (average grain size = 827 nm) 10:90 Example 12 Alumina (average particle size = 1.3 μm) 30:70

[0210] Table 7

[0211]

[0212] The results in Table 6-7 show that by replacing some of the porous cellulose particles with inorganic heat-resistant particles, a separator with excellent liquid absorption and retention rates as well as shrinkage rates in the MD and TD directions can also be obtained, and the cycle performance of the final battery is even better.

[0213]

[0214] Examples 13-16

[0215] Examples 13-14 differ from Example 1 in that they use different weight ratios of alkali, urea, and cellulose. Examples 15-16 differ from Example 1 in that they use different solid contents of the cellulose dispersion. See Table 8 for details. The characterization and performance test data of the separating membrane are shown in Table 9.

[0216] Table 8

[0217]

[0218] Table 9

[0219]

[0220]

[0221] As shown in Table 8, when the weight percentage of alkali and urea is relatively high, the sphericity of the porous cellulose granules is relatively high, while the average particle size is relatively small. Furthermore, when the solid content of the cellulose dispersion decreases, the sphericity and porosity of the porous cellulose granules decrease, while the average particle size increases.

[0222] The results in Table 9 show that when the porosity of the coating increases, the liquid absorption and retention rates of the separator increase, the shrinkage rates in the MD and TD directions increase slightly, and the cycle performance of the final battery improves. Conversely, when the sphericity of the porous cellulose particles in the coating decreases, the liquid absorption rate of the separator decreases, the liquid retention rate increases slightly, the shrinkage rates in the MD and TD directions decrease, and the cycle performance of the final battery slightly decreases.

[0223] Although this application has been described with reference to preferred embodiments, various modifications can be made thereto and components can be replaced with equivalents without departing from the scope of this application. In particular, the technical features mentioned in the various embodiments can be combined in any manner, provided there is no structural conflict. This application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.

Claims

1. A battery cell, comprising a positive electrode, a negative electrode, and a separator between the positive electrode and the negative electrode, the separator comprising a base film and a coating on at least one side of the base film, wherein, The coating comprises porous cellulose particles.

2. The battery cell according to claim 1, wherein, The porous cellulose particles are spherical or near-spherical particles.

3. The battery cell according to claim 1 or 2, wherein, The sphericity of the porous cellulose particles is 0.83-0.

91.

4. The battery cell according to any one of claims 1 to 3, wherein, The average particle size of the porous cellulose particles is 10-16 μm.

5. The battery cell according to any one of claims 1 to 4, wherein, The porous cellulose particles include any one or more of plant cellulose particles or bacterial cellulose fiber particles.

6. The battery cell according to any one of claims 1 to 5, wherein, The coating also includes inorganic heat-resistant particles.

7. The battery cell according to claim 6, wherein, The weight ratio of the porous cellulose particles to the inorganic heat-resistant particles in the coating is 10-60:90-40, or optionally 30-60:70-40.

8. The battery cell according to any one of claims 1 to 7, wherein, The porosity of the isolation membrane is 44%-53%.

9. A method for preparing a battery cell, comprising a process for preparing a separator, the preparation process comprising: Raw materials including porous cellulose particles, dispersants and binders are mixed to obtain a slurry; and The slurry is placed on at least one side of the base membrane and dried to obtain the separator membrane.

10. The preparation method according to claim 9, wherein, The preparation process also includes a process for preparing porous cellulose particles, which includes: Cellulose is dissolved and dispersed to obtain a cellulose dispersion. The cellulose dispersion was frozen and then thawed. The thawed cellulose dispersion was dried to obtain porous cellulose particles.

11. The preparation method according to claim 10, wherein, The solid content of the cellulose dispersion is 5 wt% to 25 wt%.

12. The preparation method according to claim 10 or 11, wherein, The process of dissolving and dispersing cellulose includes: Alkali, urea, and cellulose are mixed with water to form a cellulose dispersion. Optionally, the process of dissolving and dispersing cellulose also satisfies one or more of the following conditions: The weight ratio of alkali, urea and cellulose is (5-15):(5-25):(1-10); The cellulose is one or more of plant cellulose and bacterial cellulose fibers.

13. The preparation method according to any one of claims 10 to 12, wherein, The process of drying the thawed cellulose dispersion to obtain porous cellulose particles includes: The thawed cellulose dispersion was subjected to a first drying process to obtain initial cellulose particles. The initial cellulose particles are washed with water and then subjected to a second drying process to obtain the porous cellulose particles.

14. The preparation method according to claim 13, wherein, The first drying method is spray drying.

15. The preparation method according to any one of claims 9 to 14, wherein, A portion of the porous cellulose particles were replaced with inorganic heat-resistant particles.

16. The preparation method according to claim 15, wherein, The weight ratio of the porous cellulose particles to the inorganic heat-resistant particles is (10-60):(90-40), optionally 30-60:70-40.

17. A separating membrane comprising a base membrane and a coating located on at least one side of the base membrane, wherein, The coating comprises porous cellulose particles.

18. The separator membrane according to claim 17, wherein, The porous cellulose particles are spherical or near-spherical particles.

19. The separator according to claim 17 or 18, wherein, The sphericity of the porous cellulose particles is 0.83-0.

91.

20. The separator membrane according to any one of claims 17 to 19, wherein, The average particle size of the porous cellulose particles is 10-16 μm.

21. The separator membrane according to any one of claims 17 to 20, wherein, The coating also includes inorganic heat-resistant particles.

22. The separator according to claim 21, wherein, The weight ratio of the porous cellulose particles to the inorganic heat-resistant particles in the coating is (10-60):(90-40), optionally 30-60:70-40.

23. A battery device comprising a battery cell according to any one of claims 1 to 8 or a battery cell prepared by any one of claims 9 to 16.

24. An electrical device comprising a battery cell according to any one of claims 1 to 8, a battery cell prepared by any one of claims 8 to 16, or a battery device according to claim 23.